AJARAN TAREKAT SYEKH AHMAD AT-TIJANI: ANALISIS MATERI DAKWAH - Choiriyah Choiriyah (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2013)
“Tarekat” is an institution that was raised as a medium for the servant of God who wants to achieve closeness to Allah and His Messenger, as did the Tijaniyah tarekat. In Tijaniyah congregation to reach these goals Sheikh Ahmad at-Tijani as the founder of the congregation Tijaniyah teach three different forms of remembrance, remembrance lazimah ie, Hailalah and wadzifah. The material contained in dakwah remembrance (zikr) is to invite people to a certain character to God with repentance istighfar begged forgiveness to God. Invite to multiply read Sholawat to the Prophet as well as materials related to faith.